Chemerin and Dermcidin in Human Milk and Their Alteration in Gestational Diabetes. (August 2019) - Ustebay, Sefer; Baykus, Yakup; Deniz, Rulin; Ugur, Kader; Yavuzkir, Seyda; Yardim, Meltem; Kalayci, Mehmet; Çaglar, Mete; Aydin, Suleyman
Background: Chemerin and dermcidin, which have antimicrobial properties, are molecules that are also related to insulin resistance and inflammation. Research aims: The aims were to determine the amounts of chemerin and dermcidin in the milk and blood of mothers with gestational diabetes, and to compare the amounts of chemerin and dermcidin in the milk and blood of mothers with and without diabetes. Methods: This was a two-group nonrandomized longitudinal study with a convenience sampling of mothers without gestational diabetes ( n = 27) and mothers with gestational diabetes ( n = 26). Human milk and blood samples were obtained from these mothers during colostrum, transitional, and mature milk periods. The amount of chemerin and dermcidin in these samples was measured by enzyme-linked immunosorbent assay. Results: The presence of chemerin and dermcidin was first detected in human milk. The amounts of chemerin and dermcidin in the blood of all the mothers were greater in the colostrum period and lowest in the mature period. The amount of chemerin and dermcidin in the milk of all the mothers was greater than that in the blood. The amounts of chemerin and dermcidin were significantly increased in both blood and human milk within the gestational age samples. Conclusions: Chemerin and dermcidin may contribute to the protection of infants from infections during infancy. Increased amounts of these molecules found within the gestational diabetes group may also prevent adverse maternal and fetal outcomes.